HOW AN EX-CONVICT CHILD SURVIVES: Self-Conception, Symbolic Interaction, and Interpersonal Communication - Saputra, Edrizal; Putri, Dianingtyas M. (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
This article analyzes the process of forming RF’s self-concept before and after he was in Lembaga Pembinaan Khusus Anak (LPKA), the term for juvenile prison. The analysis uses the theory of symbolic interactionism by George Herbert Mead, dimensions of self-concept by Fitts, and interpersonal communication by Joseph A. DeVito, with a single case study method. The results showed that the self-concept of RF tends to be positive during and after leaving LPKA. The internal dimensions of RF’s self-concept are his emotionally intelligent identity and achievers; that behavior shows his positive self-disclosure and self-acceptance. Meanwhile, the external RF’s self-concept dimension is physical self-concept and confidence in his appearance. His self-concept speaks of happiness in public. RF’s social self-concept is happy to socialize with everyone, RF’s moral self-concept is that RF feels patient, and RF’s family self-concept is to help his family economy with halal work. In interpersonal communication, RF is now good at communicating his uniqueness, making reputation enhancements with a positive self-concept, and has made his work environment a lively community.To cite this article (7th APA style): Saputra, E. & Putri, D. M. (2021). How an ex-convict child survives: Self-conception, symbolic interaction, and interpersonal communication. Journal Communication Spectrum: Capturing New Perspectives in Communication, 11(2), 95-107. http://dx.doi.org/10.36782/jcs.v11i2.2025